2013
DOI: 10.1254/jphs.13093fp
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to Low-Dose Bisphenol A Impairs Spatial Learning and Memory in Male Rats

Abstract: Abstract. Bisphenol A (BPA) is an estrogenic endocrine disruptor used for producing polycarbonate plastics and epoxy resins. This study investigated the effects of perinatal BPA exposure on learning and memory, general activity, and emotionality in male Sprague Dawley rats using a battery of behavioral tests, including an appetitemotivated maze test (MAZE test) used to assess spatial learning and memory. Mother rats were orally administered BPA (50 or 500/day) from gestational day 10 to postnatal day 14. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Many studies have reported the non-monotonic dose-response of environmental endocrine disruptors such as BPA and diethylstilbestrol (DES) [25,34]. Additionally, it has been suggested that phytoestrogens exert weak estrogenic effects at low concentrations and antiestrogenic effects at high concentrations [21,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported the non-monotonic dose-response of environmental endocrine disruptors such as BPA and diethylstilbestrol (DES) [25,34]. Additionally, it has been suggested that phytoestrogens exert weak estrogenic effects at low concentrations and antiestrogenic effects at high concentrations [21,35].…”
Section: Discussionmentioning
confidence: 99%
“…We used the MAZE test as an estimate of spatial learning and memory as described before [25]. The MAZE apparatus was painted white and consisted of a large compartment (90 × 90 × 50 cm) with an attached goal partition (15 × 15 × 50 cm).…”
Section: Maze Testmentioning
confidence: 99%
“…Prenatal (and postnatal) exposure to environmentally relevant doses of BPA through the maternal diet decreased spatial navigation and memory in male deer mice when tested as adults in the Barnes maze [14,15]. Alterations of spatial learning and memory were also reported in male rats [23] and mice [24••] perinatally exposed to BPA. Two human epidemiological studies attempted to correlate gestational BPA exposure with children cognitive responses but reached conflicting conclusions; one study reported significant BPA-associated cognitive impairments [25], while the other failed to find any correlation [26].…”
Section: Behaviormentioning
confidence: 99%
“…Therefore, our results suggest a non-monotonic dose-response effect of NP on spatial learning and memory performance in male rats. In our previous studies, we evaluated the non-monotonic dose-response relationship between perinatal exposure to bisphenol A (BPA) and spatial learning and memory (Kuwahara et al, 2013). BPA is also one of the most commonly encountered environmental endocrine disruptors with a very weak estrogenic activity.…”
Section: Discussionmentioning
confidence: 99%